Functions: Fractional functions
Inverse of linear fractional function
We have seen that determining the inverse function is the same as isolating the variable #x# in a formula of the form #y=\ldots#. Now we will investigate how to do that for linear fractional functions.
Procedure We determine the inverse function of the linear fractional function #\green{y}=\frac{a\blue{x}+b}{c\blue{x}+d}# with #a#, #b#, #c# and #d# as numbers. 
Example #\green{y}=\frac{2\blue{x}5}{3\blue{x}+2}# 

Step 1  Multiply by the denominator of the fraction: #c\blue{x}+d#.  #\green{y} \left(3\blue{x}+2\right)=2\blue{x}5# 
Step 2  Expand the brackets.  #3\blue{x}\green{y}+2 \green{y}=2\blue{x}5# 
Step 3  By means of reduction move the terms without #x# to the right and the terms with a #x# to the left hand side.  #3\blue{x}\green{y}2\blue{x}=2 \green{y}5# 
Step 4  Move #x# outside brackets.  #\blue x \left(3 \green{y}2\right)=2 \green{y}5# 
Step 5  Divide by what's in between the brackets, so that we only have #x# at the left hand side.  #\blue x=\frac{2 \green{y}5}{3 \green{y}2}# 
Step 6 
Swap the #\blue x# into a #\green y# and the #\green y# into a #\blue x# to get the inverse function. 
#\green y=\frac{2 \blue{x}5}{3 \blue{x}2}# 
Isolate #x# in
\[y={{4\cdot x+3}\over{2\cdot x+3}}\]
\[y={{4\cdot x+3}\over{2\cdot x+3}}\]
#x={{33\cdot y}\over{2\cdot y4}}#
#\begin{array}{rcl}
y&=&{{4\cdot x+3}\over{2\cdot x+3}} \\ &&\phantom{xxx}\blue{\text{the original function }}\\
y \cdot \left(2\cdot x+3\right)&=& 4\cdot x+3 \\ &&\phantom{xxx}\blue{\text{both sides divided by }2\cdot x+3}\\
2\cdot x\cdot y+3\cdot y&=&4\cdot x+3 \\ &&\phantom{xxx}\blue{\text{brackets expanded}}\\
2\cdot x\cdot y4\cdot x &=&33\cdot y \\&&\phantom{xxx}\blue{\text{terms with } x \text{ to the left hand side, terms without }x \text{ to the right hand side }}\\
x\cdot \left(2\cdot y4\right) &=& 33\cdot y \\ &&\phantom{xxx}\blue{x \text{ moved outside brackets}}\\
x&=&{{33\cdot y}\over{2\cdot y4}} \\ &&\phantom{xxx}\blue{\text{divided by }2\cdot y4}\\
\end{array}#
#\begin{array}{rcl}
y&=&{{4\cdot x+3}\over{2\cdot x+3}} \\ &&\phantom{xxx}\blue{\text{the original function }}\\
y \cdot \left(2\cdot x+3\right)&=& 4\cdot x+3 \\ &&\phantom{xxx}\blue{\text{both sides divided by }2\cdot x+3}\\
2\cdot x\cdot y+3\cdot y&=&4\cdot x+3 \\ &&\phantom{xxx}\blue{\text{brackets expanded}}\\
2\cdot x\cdot y4\cdot x &=&33\cdot y \\&&\phantom{xxx}\blue{\text{terms with } x \text{ to the left hand side, terms without }x \text{ to the right hand side }}\\
x\cdot \left(2\cdot y4\right) &=& 33\cdot y \\ &&\phantom{xxx}\blue{x \text{ moved outside brackets}}\\
x&=&{{33\cdot y}\over{2\cdot y4}} \\ &&\phantom{xxx}\blue{\text{divided by }2\cdot y4}\\
\end{array}#
Unlock full access
Teacher access
Request a demo account. We will help you get started with our digital learning environment.
Student access
Is your university not a partner?
Get access to our courses via Pass Your Math independent of your university. See pricing and more.
Or visit omptest.org if jou are taking an OMPT exam.
Or visit omptest.org if jou are taking an OMPT exam.